2011
DOI: 10.1007/978-1-4419-5632-3_12
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Innate Immune Effector Mechanisms in the Formulation of a Vaccine Against HIV-1

Abstract: The realization of a major role for events that occur during acute viremia that dictate the course of disease both in HIV-1 infected humans and susceptible SIV infected non-human primates has prompted an intense interest in studies of the contribution of innate immune effector mechanisms. It is reasoned that findings from such studies may be important and need to be incorporated into the design and formulation of potential candidate vaccines against HIV-1. This review serves to outline the various non-human pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Our lab and others have shown that SIV infection of Rhesus macaques is a valuable tool to mimic natural HIV infection in humans (Pegu, Vaccari et al, 2012; Morgan, Marthas et al, 2008; Ansari, Mayne et al, 2011). The majority of HIV infections are acquired through sexual transmission, thus HIV enters the body through the vaginal, rectal, or penile mucosa.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our lab and others have shown that SIV infection of Rhesus macaques is a valuable tool to mimic natural HIV infection in humans (Pegu, Vaccari et al, 2012; Morgan, Marthas et al, 2008; Ansari, Mayne et al, 2011). The majority of HIV infections are acquired through sexual transmission, thus HIV enters the body through the vaginal, rectal, or penile mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…The early phase of HIV infection is critical as the outcomes of the interaction between the virus and the immune system during this phase is likely to determine whether the virus is eliminated, locally controlled, or disseminates to the rest of the body (Naranbhai, Altfeld et al, 2013; Ansari, Mayne et al, 2011). While it is clear that there is a rapid activation of innate immune responses after viral exposure (Chang & Altfeld, 2010; Haase, 2010) details on innate cell types and their role in the immune responses to HIV remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations